Computed tomography imaging of a leopard tortoise (Geochelone pardalis pardalis) with confirmed pulmonary fibrosis: a case report - Lim, Chee Kin (BioMed Central, 2013)
An approximately 20-year-old, female Leopard tortoise (Geochelone pardalis pardalis) was presented with dypsnea, wheezing, anorexia and depression. Whole body radiographs revealed generalized diffuse unstructured ‘interstitial lung pattern’ with thickened pulmonary septae while computed tomography (CT) showed emphysematous lung parenchyma and thickened pulmonary septae bordered by irregular ground-glass opacity with smaller areas of ‘honeycombing’. These imaging findings together with histopathologic findings were compatible with chronic, extensive ‘interstitial’ pulmonary fibrosis.